Preparing Counsellors for Interprofessional Collaboration through Supervision and Lateral Mentoring - Arthur, Nancy; Russell-Mayhew, Shelly (Canadian Journal of Counselling and Psychotherapy, 2010)
Interprofessional collaboration is emerging as a best practice in health care. For counsellors to work effectively alongside professionals from other disciplines, they need to be educated about the value of collaborative practice and the roles, responsibilities, and expertise that they bring to interprofessional teams. Supervision practices in counsellor education can be leveraged to help counsellors acquire competencies for learning with and from other professionals. The advantages and challenges of interprofessional supervision are discussed, offering suggestions for counsellor education. Lateral mentoring is introduced as a supervision practice through which students benefit from exposure to the perspectives of professionals from other disciplines.